Assessment of learning in online academic programs from the digital transformation impelled by Covid-19 - Paredes-Chacín, Ana Judith; Vargas-Escobar, Luz Adriana; Inciarte-González, Alicia; Mercado-Porras, Carolina (Revista de Ciencias Sociales, 2023)
The objective of the study is to determine the stages of the evaluation of learning in online academic programs as a result of the digital transformation impelled by the Covid-19 pandemic in higher education. It is based on the digital transformation adopted in higher education since the Covid-19 pandemic, which accelerated the renewal of existing curricular programs and teaching-learning processes with a fragmented evaluation process. Through an explanatory research - purposeful and qualitative approach, the variables and metric indicators of pertinence, relevance and frequency of production of literature associated with the theme are studied to process the data. Likewise, a questionnaire was designed for the pilot study, selecting 25 teachers as sample units from two accredited private higher education institutions in Colombia located in Santiago de Cali and Barranquilla. The findings determined a 0.946 margin of reliability of the instrument for its application in the second phase and a matrix of indicators and the system of relations on the components and stages of the evaluation system were generated. The systematized practice of the stages is proposed as a conclusive basis for the definition of metrics that determine the incidence on the application of the evaluation of learning from academic programs mediated by digital technologies.